Photoinduced Electron Transfer in Perylene-TiO2 Nanoassemblies - Llansola Portolés, Manuel Jose (2013)
The photosensitization effect of three perylene dye derivatives on titanium dioxide nanoparticles (TiO2 NPs) has been investigated. The dyes used, 1,7-dibromoperylene-3,4,9,10-tetracarboxy dianhydride (1), 1,7-dipyrrolidinylperylene-3,4,9,10-tetracarboxy dianhydride (2) and 1,7-bis(4-tert-butylphenyloxy)perylene-3,4,9,10-tetracarboxy dianhydride (3) have in common bisanhydride groups that convert into TiO2 binding groups upon hydrolysis. The different substituents on the bay position of the dyes enable tuning of their redox properties to yield significantly different driving forces for photoinduced electron transfer (PeT). Recently developed TiO2 NPs having a small average size and a narrow distribution (4 ± 1 nm) are used in this work to prepare the dye-TiO2 systems under study. Whereas successful sensitization was obtained with 1 and 2 as evidenced by steady-state spectral shifts and transient absorption results, no evidence for the attachment of 3 to TiO2 was observed. The comparison of the rates of PeT (kPeT) for 1- and 2-TiO2 systems studied in this work with those obtained for previously reported analogous systems, having TiO2 NPs covered by a surfactant layer (Hernandez et al. [2012] J. Phys. Chem. B., 117, 4568–4581), indicates that kPeT for the former systems is slower than that for the later. These results are interpreted in terms of the different energy values of the conduction band edge in each system.